A study to develop in vivo determination of platelet activation markers by flow cytometer - Jamaludin, Normah (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2003)
Abstract Introduction. Pre-menopausal women have lower risk of cardiovascular disease compared to post menopausal women which is more age dependent in women than in men. Increased and disturbed platelet activation plays a major role in the pathophysiology of thrombosis and has been noted in different thrombotic disorders. Temporal association between cardiovascular disease and increased platelet activation is well established. The role of platelet activation needs to be evaluated in this population. Methods. Evaluation of Platelet activation markers was done in 49 post-menopausal (56.16 ± 0.83 years; mean± SEM) and 42 pre menopausal women (39.38years ± 1.09). Subjects were recnuted after informed verbal consent. The technique used for in vivo evaluation. of platelet Activation Markers by Flow cytometer using 3-color analysis (CD61 PerCP, CD62P and PACI) was previously developed and optimized. Blood· samples were drawn in a standardized manner to minimize in vitro activation of platelets. Samples were processed and analyzed in duplicate. Results. There was a significant increase in CD62P in post-menopausal women as compared to the control (pre-menopausal) group (7.28 ± 1.63 vs 0.8887 ± 0.1922; mean± SEM, p=O.OOI). Similarly PACI were significantly increased in post-menopausal group (29.45 ± 3.04 ·vs 5.22 ± 0.710; p<O.OOI). However there was no significant correlation between CD62P or PACl markers wit1Ls_ellll1L.1riglycerides,_:_estradiol-and-bod.Y-tnas~---- index in both groups. ·- Conclusion. ~latelet Activation markers CD62P and PACI are increased in postmenopausal women as compared to premenopausal women. These results may suggest a role in high incidence of cardiovascular disease in this group.